TEKNIK KULTUR CHAETOCEROS SP. SEBAGAI PAKAN ALAMI LARVA UDANG VANAMEI (LITTOPENAEUS VANNAMEI) DI BPIU2K KARANGASEM BALI - NINGRUM, REMA APRIA; DINIARIWISAN, DAMAI (GANEC SWARA, 2024)
The larval stages in vannamei shrimp can be referred to as vulnerable stages that are prone to experiencing environmental crises, mainly due to the inadequate availability of food. Chaetoceros sp. is commonly used as a natural food source because it contains high nutrition that fulfills the larva's requirements for survival. However, the lack of proficiency in proper culture techniques impacts the success of cultivating Chaetoceros sp. as natural food. The objective of this study is to understand the culture techniques and challenges in cultivating natural food and to assess the effects of feeding Chaetoceros sp. on vannamei larvae (Litopenaeus vannamei). The data obtained in this study were analyzed descriptively, meticulously presenting the findings in a clear manner. In laboratory-scale Erlenmeyer culture, the peak plankton growth reached 15.3 million cells/mL, whereas in the Carboy, the density reached up to 5.1 million cells/ml. On the intermediate scale, plankton growth started at 550,000 cells/ml on the first day and increased to 1.8 million cells/mL on the eighth day. The effect of feeding Chaetoceros sp. as natural food source for vannamei larvae resulted in meeting the nutritional needs for the shrimp's body, contributing to the larval development with a relatively high survival rate of approximately 85%.